Mechanical Properties of Phagraphene Membranes: A Fully Atomistic Molecular Dynamics Investigation. (15th January 2018) - de Sousa, J. M.; Aguiar, A. L.; Girão, E. C.; Fonseca, Alexandre F.; Filho, A. G. Sousa; Galvao, Douglas S.
ABSTRACT: Recently, a new 2D carbon allotrope structure, named phagraphene (PG), was proposed. PG has a densely array of penta-hexa-hepta-graphene carbon rings. PG was shown to present low and anisotropic thermal conductivity and it is believed that this anisotropy should be also reflected in its mechanical properties. Although PG mechanical properties have been investigated, a detailed and comprehensive study is still lacking. In the present work we have carried out fully atomistic reactive molecular dynamics simulations using the ReaxFF force field, to investigate the mechanical properties and fracture patterns of PG membranes. The Young's modulus values of the PG membranes were estimated from the stress-strain curves. Our results show that these curves present three distinct regimes: one regime where ripples dominate the structure and mechanical properties of the PG membranes; an elastic regime where the membranes exhibit fully planar configurations; and finally am inelastic regime where permanent deformations happened to the PG membrane up to the mechanical failure or fracture.